1992
DOI: 10.1093/jn/122.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Alters DMBA-Induced Tumor Burden and Natural Killer Cell Cytotoxicity in Rats

Abstract: Natural killer (NK) cell activity is impaired in iron-deficient rats. Natural killer cells destroy tumor cells; therefore, iron-deficient rats may be less able to combat cancer growth. Natural killer cell cytotoxicity, both basal and interferon gamma (IFN gamma)-stimulated, was studied in moderately and severely iron-deficient rats challenged with the carcinogen 7,12-dimethylbenz[a]anthracene (DMBA). Female weanling rats were fed ad libitum semipurified diets containing 8, 13 or 42 mg Fe/kg. A pair-fed group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…These results suggested that iron deficiency leads to impaired T-cell response. Another study showed that NK cell cytotoxicity was impaired in rats fed an iron-deficient diet, and adding IFN-g in vitro rescued the loss of function (42).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…These results suggested that iron deficiency leads to impaired T-cell response. Another study showed that NK cell cytotoxicity was impaired in rats fed an iron-deficient diet, and adding IFN-g in vitro rescued the loss of function (42).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Macrophage phagocytosis is generally unaffected by iron defi ciency, but bactericidal activity of these macrophages is shown to be attenuated in some studies. Neutrophils have a reduced activity of myeloperoxidase, an iron-containing enzyme, which produces reactive oxygen intermediates responsible for intercellular killing of pathogens [6]. Moreover, in vitro studies have shown that there is a direct link between iron defi ciency and impaired T-lymphocyte proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils have a reduced activity of myeloperoxidase, an iron-containing enzyme which produces reactive oxygen intermediates (ROI) that are responsible for intracellular killing of pathogens. 13 In vitro studies have shown that there is a direct correlation between iron deficiency and impaired T-lymphocyte proliferation. There is a decrease in T-lymphocyte blastogenesis and mitogenesis in response to a number of different mitogens.…”
Section: Discussionmentioning
confidence: 99%